Photophysics, Photochemical and Substitution Reactions Recent Advances - Saha, Satyen; Kumar Kanaparthi, Ravi; Soldatovi?, Tanja V. (IntechOpen, 2021)
This book represents a unique blend of topics covering photon-initiated reactions to substitution reactions. Additionally, several fantastic chapters on the photophysics of popular dyes and their applications make the book interesting for researchers working on photon-initiated physical and chemical processes.